Complex Discrete System Analysis of Process Design and Tourist Souvenir Making Based on Artificial Intelligence 3D Printing - Yuchuan Guo (Discrete Dynamics in Nature and Society)
With the rapid development of 3D (three-dimensional) printing technology, it has been widely used in the field of ceramic arts and crafts. However, due to the complexity of 3D printing technology, it will face complex modeling and calculation when designing ceramic art crafts. To this end, the artificial intelligence algorithm is introduced, and using the data measured by the built-in modeling instruction of LAMMPS of the artificial intelligence algorithm, the program is used to reset its coordinates, length, width, height, and focal length. The obtained data are modified by postprocessing to correct its coordinates and the size of the simulation frame, so that the nanopowder model is placed in the center, forming a solid ellipsoidal aluminum nanopowder and cutting it into a three-dimensional model of teapot, which is transformed into the STL file of two-dimensional cross section, and the finished product is printed out to the 3D printer. Finally, the RTM model is used to test the quality of tourist souvenirs. The results show that the homogeneity of variance is much greater than 0.10. It can be inferred that the tourist souvenirs of pottery teapots have met the requirements of national technological quality standards.